Core Learning Model and Mathematical Disposition, Against Mathematics Problem Solving Ability of Elementary School Students - Sonny Irawan; Vina Iasha (Buana Pendidikan, 2021)
This research is aimed to reveal the effects of the core learning model and mathematical disposition model to problem-solving skills in elementary school. This research is experimental research with a 2x2 factorial design. The research sample is fourth-grade students, i.e., 44 persons. The instrument is the mathematical disposition and problem-solving skill instrument. The research result shows that the core learning model is a suitable mathematical learning model to develop mathematical problem-solving skills. The core learning model is more appropriately applied on a group of students with a high mathematical disposition. Meanwhile, the conventional model is more suitable to be applied on a group of students with a low mathematical disposition